Forming the geometric accuracy and roughness of holes when drilling aircraft structures made from polymeric composite materials - Kateryna Maiorova (Eastern-European Journal of Enterprise Technologies, 2022)
The subject of this study is indicators of the quality, geometric accuracy, and roughness of holes in aviation structures (AS) made from polymeric composite materials (PCM) produced by drilling. The indicators of quality, geometric accuracy, and roughness of PCM holes were investigated by using kinematic hole drilling schemes and the creation of PCM chips. A kinematic scheme has been built of the cutting forces operating in PCM when drilling with the distribution of zones from 0° to 360°. Experimental studies on the establishment of characteristic shrinkage zones in the drilling of PCM, as well as their values, have been implemented. The methods used are the analysis of the quality indicators of PCM holes, and the method of expert assessments. The following results were obtained. Based on the analysis and synthesis, it was found that with incorrectly selected geometric parameters for drills involving the work accompanied by the wear of drills on the back surface, stratification, cracks, or chips of PCM may appear. It is shown that the decisive factor is a comprehensive assessment, which is determined not only by the quality, accuracy, and roughness but also by the condition of the holes at the input and output of the drill. Features and characteristic contact zones for PCM drilling were identified. It has been established that within the drill operating areas from 0° to 90° and from 180° to 270° the cutting forces are reduced while the indicators of surface quality, roughness, and geometric accuracy of a PCM hole are improved. In zones from 90° to 180° and from 270° to 360° – on the contrary, low quality of the machined surface is assumed. The calculation of the required cutting forces and calculation of the height of roughness of drilling holes in PCM have been proposed, taking into consideration the bearing of chips under the action of the wedge. The results of experimental studies on the establishment of characteristic shrinkage zones when drilling PCM confirmed the adequacy of the results of theoretical studies on the kinematic schemes of drill operation in PCM